Canal mandibular e osteotomia sagital bilateral da mandíbula : uma análise topográfica - Gondim, Ricardo Franklin (2015)
A bilateral sagittal split osteotomy of the mandible (BSSO) is performed for correction of dentofacial deformities and can be used to make forward and retract movements and for changes in the occlusal plane. In an attempt to protect the inferior alveolar nerve, the surgeon makes the osteotomy so that there is no exposure of such a structure at the time of separation of the segments. Despite having facial differences and the relationship of occlusion, Class I, II and III patients are subject to the same surgical technique without changes to adapt to the peculiarities of each case. The mandibular canal ratio analysis with the design of the BSSO can provide important information to enable the professional to set standards and osteotomy levels for each type of malocclusion. Objective: To analyze bilaterally, using cone beam computed tomography (CBCT), the topography of the mandibular canal of a sample of patients undergoing orthognathic surgery. Methods: 444 CBCT in the preoperative phase who underwent orthognathic surgery with the use of the BSSO from 2009 to 2014 were analysed according the inclusion and exclusion criteria, of which 213 were studied. The classification of patients according to malocclusion was based on the mesiodistal relationship of the upper and lower canines, using intraoral photos. Points located in the mandibular foramen, the anterior border of the mandible, distal second molar and interproximal first and second lower molar bilaterally served as a reference to perform the measurements. The software Dolphin Imanging 3D ®, version 11.7 was used for the measurements. Data analysis were performed with the Statistical Packcage software for the Social Sciences®, version 17.0 with a 95% confidence interval. In statistical associations were used the Kolmogorov-Smirnov normality tests, Mann-Whitney, Wilcoxon or Kruskal-Wallis. Results: Patients class III had bilateral reduction in bone height in the regions of anterior border of the mandibular branch, distal second molar and between the molars. Also had bilateral reduced bone thickness in the anterior border of the mandibular ramus. Class II patients showed increased thickness of the base jaw. As the distance of the second molar in relation to the mandibular lingula, class II patients had lower height, and class III patients had greater height. Conclusion: The mandibular canal showed topographical differences between the types of malocclusion, suggesting the need to differentiate the depth and the thickness of the bone cuts. Future studies with individualized osteotomies for the types of malocclusion are required to verify the clinical application of the findings of this research.